Interprofessional education and collaboration between general practitioner trainees and practice nurses in providing chronic care; a qualitative study - R. van der Gulden; N. D. Scherpbier-de Haan; C. M. Greijn; N. Looman; F. Tromp; P. W. Dielissen (BMC Medical Education, 2020)
Abstract Background Effective interprofessional collaboration (IPC) is essential for the delivery of chronic care. Interprofessional education (IPE) can help support IPC skills. This makes IPE interesting for GP practices where chronic care is delivered by GPs together with practice nurses, especially for GP trainees who have to learn to collaborate with practice nurses during their training. The aim of this study is to gain insights in how IPE and IPC occur between GP trainees and practice nurses during the delivery of chronic care in GP training practices. Methods We conducted a qualitative research using semi structured focus groups and interviews with GP trainees, practice nurses and GP supervisors. All respondents were primed to the subject of IPE as they had followed an interprofessional training on patient-centred communication. The verbatim transcripts of the focus groups and interviews were analysed using thematic analysis. Results Despite the overall positive attitude displayed by respondents towards IPE and IPC, the occurrence of IPE and IPC in GP training practices was limited. Possible explanations for this are impeding factors such as limited knowledge, prejudice, lack of role models and a hierarchical organisational structure. Contributing to IPE and IPC use was the integration of IPE in daily practice, e.g. via recurring scheduled meetings. Conclusion We found a limited occurrence of IPE and IPC in GP training practices. Our results show a discrepancy between respondents enthusiasm for IPE and IPC and their actual behaviour. IPE activities have to be initiated in GP training practices, otherwise, despite good intentions, IPE and IPC will be ineffective.